STROKE CARE: STROKE UNIT VERSUS NON STROKE UNIT - Widy Hartono; Ede Surya Darmawan (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Stroke is one of the leading causes of death and long-term disability in adults. A comprehensive and integrated stroke unit care plays an important role to reduce these burdens. This paper aims to describe the difference in outcomes between stroke care in stroke units and non-stroke units as information basis to encourage hospitals to establish this service. Methods: This review is done based on research articles on stroke treatment outcomes in the stroke unit. The literature search was conducted in December 2017 to May 2018 through University of Indonesia's online library and Google Scholar. Five articles are selected based on predetermined criteria. Articles that examined comparison of stroke treatment outcomes in stroke units with non- stroke units were selected and analyzed. Results: Many studies have shown that stroke treatment in the stroke unit provides better outcomes compared to other non-stroke units. Treatment in the stroke unit improves survival and independency, decreases mortality and disability and shortens length of stay in the hospital. Conclusion: The stroke unit is an important part of stroke management because it provides comprehensive and integrated services that resulting in better treatment outcomes. Stroke unit will increase hospital credibility.